Influence Of Process Parameter On The Height Deviation Of Weld Bead In Wire Arc Additive Manufacturing - Rosli, Nor Ana; Abdollah, Mohd Fadzli; Alkahari, Mohd Rizal; Ramli, Faiz Redza (TJPRC Pvt. Ltd., 2020)
Significant attention towards Wire and Arc Additive Manufacturing (WAAM) has gradually increased. WAAM technology has been proven in building three-dimensional (3D) metal parts efficiently and economically. The combination of wire and arc welding is promising, especially in depositing metals with higher deposition rate, and low cost of raw materials, as well as manufacturing of a large-scale product. However, there are several process parameters should be optimized to ensure no internal defect, acceptable surface finish and consequently to have a good quality of final parts when using WAAM. Therefore, an experimental design using the Taguchi method was used to determine the effect of welding current, welding voltage, and travel speed on the responses, including the deviation in height were investigated. The results revealed that travel speed was the dominant factor affecting the waviness surface structure on top of the 3D metal parts. Besides, the contribution rate for each factor to the deviation in height was also determined.